Analysis of the Impact of Academic Activities on Students' Stress Levels and Mental Health - Hayatun Novi Aulia; Fadillah Sari Deswita; Lindawati Lindawati; Gunawan Gunawan (Indonesian Journal of Health and Medical Education, 2026)
This study aims to analyze the impact of academic activities on students' stress levels and mental health. The background of this study stems from the increasing academic demands that include assignment loads, tight class schedules, pressure to achieve grades, and various organizational and social responsibilities that students must face. The research method used a quantitative approach with a survey design, conducted by distributing a Google Form questionnaire to 60 respondents from various faculties at the University of Mataram and its surrounding areas. The research instrument consisted of an academic stress scale that included indicators of assignment demands, class schedules, grade pressure, time management skills, and mental well-being. The results showed that academic stress levels were in the moderately high category, with the highest average score for the tight class schedule indicator (4.03). The most dominant factors affecting student mental health were the large number of assignments and strict academic demands, followed by time management difficulties, economic pressure, and the pressure to achieve grades. Furthermore, social support was recorded as still low, exacerbating the academic stress experienced. These findings indicate the need for an evaluation of the learning system and strengthening counseling services to improve student mental well-being. This research is expected to serve as a reference for universities in designing more humane academic policies and supporting student mental health.